Neurofibromatosis type 1 – own experiences - Czajkowski, Grzegorz; Kałużny, Jakub; Jatczak-Gaca, Agnieszka; Wysocki, Mariusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: Neurofibromatosis type1 is one of the most common inherited syndromes. The aim of this study was to evaluate eye symptoms on this disease. Material and methods: 52 patients with neurofibromatosis type 1 were observed (28 males and 24 females), age between 3 and 49 years old (mean 21). The patients were divided into five groups depending on the age: 0-10 years old, 11-20 years old, 21-30 years old, 31-40 years old and older than 40 years. Frequency of the eye symptoms was estimated in each group. Results: The eye sings were observed in 69.2%. Frequency of the eye symptoms were higher in the older groups. After 21th years of age ophthalmological signs were observed in all patients. The most common were café-au-lait spots on the lids, Lisch nodules on the iris, changes in CNS , especially gliomas of the optic pathway, nodular neurofibromas in the orbit region. Conclusions: Eye signs of the disease may be noticed in the most patients with NF 1. After 21-th years of age ophthalmological symptoms are observed in all patients.The frequency of typical well known for NF 1 signs were different and characteristic for each age group.